Analysis of Factors Affecting Profitability Digital Bank In Indonesia - Suroto, Ahmad; Rahmayanti, Dewi (Publisher Cv. Inara, 2023)
Rapid technological advances in recent years have encouraged banks to become digital banks, especially after the COVID-19 outbreak which accelerated the use of digital financial services. This study aims to examine the effect of CAR, BOPO, LDR, and bank size on the profitability of digital banks in Indonesia. Profitability is measured through ROA as the dependent variable, CAR, BOPO, LDR, and bank size as independent variables. This study uses quantitative methodology using panel data regression analysis. The research sample consists of 9 digital banks (neobanks) in Indonesia selected with a purposive sampling approach. The sample selection criteria include digital banks (neobanks) that are registered in Indonesia and have disseminated quarterly financial reports from Q1 2022 to Q4 2023 in the financial statements of the Financial Services Authority (OJK). The results show that CAR has a positive and significant effect on ROA, while BOPO has a negative and significant effect on ROA. Furthermore, LDR and bank size show a favorable and sizable impact on ROA.